(untitled) (Journal of Pharmaceutical Negative Results, 2023)
A nanodrop spectrophotometric method was developed and validated for determination of Valsartan (VAL) in both bulk and tablet dosage form. Using methanol as a solvent, valsartan's maximum absorption was observed at 243 nm. The developed method was found to be linear (R2 = 0.9999) within the concentration range of 10-50 µg/mL. The precision study gives RSD less than 1%. The LOD and LOQ values were 0.34 and 1.14 g/mL, respectively. The accuracy study revealed that Valsartan commercial products had a remarkable recovery rate of more than 98%. The current method was successfully applied for valsartan stability indication study in Arbiten, Lastavin, Tabuvan, Extra, and Diostar products commonly found in pharmacies in Iraq's Kurdistan area. The stability-indicating study was investigated under acidic, basic, oxidative, photolytic, and thermal conditions. The results of all products showed that VAL is unstable in acidic, alkaline, and oxidative conditions under heating at 60℃ up to 3 hrs. While under photolytic and thermal conditions, the degradation percentage was more than 15% indicating to the instability of VAL in all products tablets in accordance to ICH International Conference on Harmonization guideline of drugs.